A comparative study to determine the short-term mortality and clinical improvement in hepatic encephalopathy using either rifaximin and or lactulose - Biswas, Uttam; Pal, Shyamal Kanti; Chaudhuri, Pallabi Ray; Roychowdhury, Debanjan; Dhar, Abhranil; Roy, Anirudhdha (Asian Journal of Medical Sciences, 2021)
Background: Hepatic encephalopathy can be reversed by correcting precipitating factors and efficiently managed by lactulose and or rifaximin. Aims and Objective: The aim of this study to compare the effectiveness of three different modes of treatment in our study populations. Materials and Methods: Ninety patients of decompensated chronic liver diseases were selected and randomised to treat with either lactulose or rifaximin or both lactulose and rifaximin (30 patients in each group) for 7 days. Clinical outcome and short term mortality were noted in each group of treatment. This study was to review the comparison of the effectiveness of Rifaximin (1200mg/day , in 3 divided doses ) alone or in combination with Lactulose (60gram/day ,in divided doses) or Lactulose (60gram/day) alone to reduce the short term mortality and clinical improvement in hepatic encephalopathy of any grade of any cause in adult (>18 years) admitted patients of decompensated chronic liver diseases. Result: Clinical improvement was noted in all three modes of treatment but there is no statistically significant difference in clinical improvement of hepatic encephalopathy when compared amongst each of three modes of treatment. There was obvious reduction of short term mortality or clinical down gradation of hepatic encephalopathy grade after 7 days treatment using lactulose or rifaximin or combined lactulose and rifaximin but there was no statistically significant difference in this regard among these three modes of treatment. Conclusion: All three modes of treatment are equally effective though combination therapy is little better.